Integrative Analysis of Bottom-Up, Top-Down, and Interactive Reading Theories in Arabic Maharah Qira'ah Learning for Non-Native Speakers - Uly Anisa Luthfi Kamilah; Cecep Sobar Rochmat (International Journal of Science and Environment (IJSE), 2026)
Arabic maharah qira’ah learning for non-native speakers still faces obstacles in text comprehension due to limited vocabulary, the complexity of language structures, and the use of learning approaches that tend to be partial rather than integrative. This study aims to analyze integratively the application of bottom-up, top-down, and interactive reading theories in maharah qira’ah learning. This study uses a descriptive qualitative approach with the library research method. Data were obtained from various literature sources such as books, scientific journal articles, and relevant previous studies, then analyzed using content analysis techniques. The results of the study show that the bottom-up approach plays a role in the gradual recognition of language elements, while the top-down approach helps comprehension through background knowledge activities, and the interactive model integrates both simultaneously. The integration of these three approaches becomes more effective when applied in systematic learning stages, namely pre-reading, during-reading, and post-reading. Thus, the integration of reading theories can be a strategic solution in developing maharah qira’ah learning that is more comprehensive, systematic, and effective for non-native speakers.